Singlet‐Contrast Magnetic Resonance Imaging: Unlocking Hyperpolarization with Metabolism. Issue 12 (11th February 2021) - Eills, J.; Cavallari, E.; Kircher, R.; Di Matteo, G.; Carrera, C.; Dagys, L.; Levitt, M. H.; Ivanov, K. L.; Aime, S.; Reineri, F.; Münnemann, K.; Budker, D.; et al.
Abstract: Hyperpolarization‐enhanced magnetic resonance imaging can be used to study biomolecular processes in the body, but typically requires nuclei such as 13 C, 15 N, or 129 Xe due to their long spin‐polarization lifetimes and the absence of a proton‐background signal from water and fat in the images. Here we present a novel type of 1 H imaging, in which hyperpolarized spin order is locked in a nonmagnetic long‐lived correlated (singlet) state, and is only liberated for imaging by a specific biochemical reaction. In this work we produce hyperpolarized fumarate via chemical reaction of a precursor molecule with para ‐enriched hydrogen gas, and the proton singlet order in fumarate is released as antiphase NMR signals by enzymatic conversion to malate in D2 O. Using this model system we show two pulse sequences to rephase the NMR signals for imaging and suppress the background signals from water. The hyperpolarization‐enhanced 1 H‐imaging modality presented here can allow for hyperpolarized imaging without the need for low‐abundance, low‐sensitivity heteronuclei. Abstract : A proton singlet state on fumarate derived from parahydrogen can be broken by enzymatic conversion to malate, which releases hyperpolarized NMR signals. We demonstrate two "out‐of‐phase echo" pulse sequences to convert the I 1z I 2z state into net proton magnetization, and show how this can be used for hyperpolarized 1 H imaging.